Chemotherapeutic drugs for soft tissue sarcomas: a review - Tian, Zhichao; Yao, Weitao (Frontiers in Pharmacology, 2023)
Despite the low incidence of soft tissue sarcomas (STSs), hundreds of thousands of new STS cases are diagnosed annually worldwide, and approximately half of them eventually progress to advanced stages. Currently, chemotherapy is the first-line treatment for advanced STSs. There are difficulties in selecting appropriate drugs for multiline chemotherapy, or for combination treatment of different STS histological subtypes. In this study, we first comprehensively reviewed the efficacy of various chemotherapeutic drugs in the treatment of STSs, and then described the current status of sensitive drugs for different STS subtypes. anthracyclines are the most important systemic treatment for advanced STSs. Ifosfamide, trabectedin, gemcitabine, taxanes, dacarbazine, and eribulin exhibit certain activities in STSs. Vinca alkaloid agents (vindesine, vinblastine, vinorelbine, vincristine) have important therapeutic effects in specific STS subtypes, such as rhabdomyosarcoma and Ewing sarcoma family tumors, whereas their activity in other subtypes is weak. Other chemotherapeutic drugs (methotrexate, cisplatin, etoposide, pemetrexed) have weak efficacy in STSs and are rarely used. It is necessary to select specific second- or above-line chemotherapeutic drugs depending on the histological subtype. This review aims to provide a reference for the selection of chemotherapeutic drugs for multi-line therapy for patients with advanced STSs who have an increasingly long survival.